Management of Non-vital Maxillary Central Incisors with Open Apices by MTA Plugging (Journal of Bangladesh College of Physicians and Surgeons, 2017)
The major challenge of performing root canal treatment in an open apex pulp-less tooth is to obtain a good apical seal. An 11 year old boy was presented with pain in his upper anterior teeth. On clinical examination both the maxillary central incisors revealed slight discoloration and fracture of the crown. Radiographic evaluation revealed radiolucency and open apices of both central incisors. Apexification with MTA apical plug was carried out before obturation with gutta-percha and sealer and the treatment was completed within 3 consecutive appointments. In twelve months follow up both the teeth were clinically and radiographically asymptomatic and the healing of the apical area was continued. The positive clinical outcome may encourage the future use of mineral trioxide aggregate (MTA) as an apical plug material in case of non-vital open apex teeth.J Bangladesh Coll Phys Surg 2017; 35(4): 196-199